Th17/Treg balance and macrophage polarization ratio in lower extremity arteriosclerosis obliterans - Zhen-Zhen Li; Min Liu; Xiong-Hui He; Zhen-Dong Liu; Zhan-Xiang Xiao; Hao Qian; You-Fei Qi; Cun-Chuan Wang (Asian Pacific Journal of Tropical Biomedicine, 2024)
Objective: To explore the balance of peripheral blood T helper 17 cells/regulatory T cell (Th17/Treg) ratio and the polarization ratio of M1 and M2 macrophages in lower extremity arteriosclerosis obliterans (ASO). Methods: A rat model of lower extremity ASO was established, and blood samples from patients with lower extremity ASO before and after surgery were obtained. ELISA was used to detect interleukin 6 (IL-6), IL-10, and IL-17. Real-time RCR and Western blot analyses were used to detect Foxp3, IL-6, IL-10, and IL-17 expression. Moreover, flow cytometry was applied to detect the Th17/Treg ratio and M1/M2 ratio. Results: Compared with the control group, the iliac artery wall of ASO rats showed significant hyperplasia, and the concentrations of cholesterol and triglyceride were significantly increased (P<0.01), indicating the successful establishment of ASO. Moreover, the levels of IL-6 and IL-17 in ASO rats were pronouncedly increased (P<0.05), while the IL-10 level was significantly decreased (P<0.05). In addition to increased IL-6 and IL-17 levels, the mRNA and protein levels of Foxp3 and IL-10 in ASO rats were significantly decreased compared with the control group. The Th17/Treg and M1/M2 ratios in the ASO group were markedly increased (P<0.05). These alternations were also observed in ASO patients. After endovascular surgery (such as percutaneous transluminal angioplasty and arterial stenting), all these changes were significantly improved (P<0.05). Conclusions: The Th17/Treg and M1/M2 ratios were significantly increased in ASO, and surgery can effectively improve the balance of Th17/Treg, and reduce the ratio of M1/M2, and the expression of inflammatory factors.